ANALISIS PENGARUH DANA PIHAK KETIGA, NON PERFORMING FINANCE MURABAHAH, DAN INFLASI TERHADAP PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH DI INDONESIA - Linda Sri Anisa; Fifi Afiyanti Tripuspitorini (Jurnal Maps (Manajemen Perbankan Syariah), 2019)
This study aims to determine how the influence of DPK, Murabaha NPF, and inflation towards Murabaha Financing partially or simultaneously at the Indonesian Sharia Commercial Bank for the period of 2016-2018. In this study, the method used is a quantitative method and uses secondary data. Secondary data were obtained from Shariah Banking Statistics reports published by the Otoiritas Jasa Keuangan (OJK) and Bank Indonesia int the period January 2016 -December 2018. The data in this study were 36 data. The technique analysis used in this study is multiple linear regression using the SPSS 23 application programs. The results of this study indicate that based on a hypothesis test that is partially (t-test) that DPK and inflation have significant negative effect on Murabahah Financing. Whereas NPF Murabaha has insignificant negative effect in Murabaha Financing. The results of the simultaneous hypothesis test (F-Test) show that DPK, NPF Murbahah, and Inflation simultaneously or together have a significant effect on Murabaha Financing.